Circulating Syndecan-1 as a Biomarker of Endothelial Injury and Survival in Hemodialysis: A Systematic Review and Meta-Analysis of Hemodynamic and Prognostic Associations - Redo Augusta M Sabebegen; Deka Viotra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Cardiovascular disease remains the primary cause of mortality in patients with end-stage renal disease (ESRD) undergoing hemodialysis (HD). Conventional risk factors fail to fully explain the high prevalence of resistant hypertension and intradialytic hemodynamic instability in this population. Emerging evidence points to the degradation of the endothelial glycocalyx (eGC), a protective luminal layer regulating vascular tone and permeability. Syndecan-1 (SDC-1), a core component of the eGC, sheds into the circulation during vascular stress. This study aimed to synthesize evidence regarding the magnitude of dialysis-induced SDC-1 shedding and its validity as a prognostic biomarker for survival and vascular stiffness. M ethods: We conducted a systematic review and associative meta-analysis of observational studies and clinical trials. We searched Scopus, PubMed, and Web of Science for studies quantifying serum SDC-1 in HD patients and relevant physiologic comparators. Data were stratified to analyze three domains: the second hit phenomenon (acute pre- vs. post-dialysis shedding), diagnostic correlations with pulse wave velocity (PWV) and fluid status, and prognostic hazard ratios (HR) for all-cause mortality. A random-effects model was employed to account for population heterogeneity, specifically stratifying hemodialysis cohorts from heart failure comparators. Results: Ten pivotal studies involving over 1,500 patients were included. The analysis confirmed a substantial acute surge in serum SDC-1 post-hemodialysis (Standardized Mean Difference = 1.24, p < 0.001), indicating that the dialysis procedure actively injures the endothelium. Elevated baseline SDC-1 correlated significantly with arterial stiffness (PWV) and sodium overload, supporting a mechanism of salt-induced vascular stiffening. In prognostic analysis, high SDC-1 was a robust independent predictor of mortality (Pooled HR = 1.65, 95% CI: 1.12–2.43). Conclusion: Hemodialysis acts as a vascular stressor, triggering acute shedding of the endothelial glycocalyx. This shedding is mechanistically linked to sodium dysregulation and vascular stiffness, independent of traditional uremic toxins. SDC-1 serves as a valuable prognostic marker for endothelial health and survival, suggesting a need for endothelium-protective dialysis strategies.